1979
DOI: 10.1111/j.1471-4159.1979.tb04552.x
|View full text |Cite
|
Sign up to set email alerts
|

PURIFICATION AND CHARACTERIZATION OF AN NADP + ‐LINKED ALCOHOL OXIDO‐REDUCTASE WHICH CATALYZES THE INTERCONVERSION OF γ‐HYDROXYBUTYRATE and SUCCINIC SEMIALDEHYDE1

Abstract: Abstract— An NADP+ ‐linked enzyme, capable of interconverting γ‐hydroxybutyrate and succinic semialdehyde, has been isolated from hamster liver and brain. The enzyme which was isolated from liver has been purified 300‐fold and exhibits a single band by polyacrylamide gel electrophoresis. The molecular weight of the enzyme is ‐ 31,000 as estimated from gel filtration and 38,000 as estimated from sodium dodccyl sulfate gel electrophoresis. The enzyme is inhibited by amobarbital, diphenylhy‐dantoin, 2‐propylvaler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
2

Year Published

1981
1981
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 31 publications
5
42
2
Order By: Relevance
“…As a consequence of GABA metabolism, SSA produced via GABA transaminase enters the TCA cycle through SSA dehydrogenase. In the central nervous system, a fraction of SSA is diverted to GHB via the NADPHdependent SSA reductase (38). GHB, a potent inhibitory neurotransmitter, is then converted back to SSA via the NAD-dependent GHB dehydrogenase (GHBDH) to form the "GHB loop" (39 -41).…”
Section: Table 1 Intracellular Amino Acid (Nmol/mg Of Islet Protein) mentioning
confidence: 99%
“…As a consequence of GABA metabolism, SSA produced via GABA transaminase enters the TCA cycle through SSA dehydrogenase. In the central nervous system, a fraction of SSA is diverted to GHB via the NADPHdependent SSA reductase (38). GHB, a potent inhibitory neurotransmitter, is then converted back to SSA via the NAD-dependent GHB dehydrogenase (GHBDH) to form the "GHB loop" (39 -41).…”
Section: Table 1 Intracellular Amino Acid (Nmol/mg Of Islet Protein) mentioning
confidence: 99%
“…Two unusual oxidoreductases, one cytosolic (19) and the other mitochondrial (20), that catalyze the oxidation of GHB to SSA have now been isolated. The cytosolic enzyme, which will be referred to as GHB-dehydrogenase in this review, was first purified to homogeneity from hamster liver (19) and was found to be an NADP+-dependent oxidoreductase. A study of the substrate specificity of purified GHB-dehydrogenase revealed that o-glucuronate and L-gulonate, the product of D-glucuronate reduction, were also good substrates (19).…”
mentioning
confidence: 99%
“…The cytosolic enzyme, which will be referred to as GHB-dehydrogenase in this review, was first purified to homogeneity from hamster liver (19) and was found to be an NADP+-dependent oxidoreductase. A study of the substrate specificity of purified GHB-dehydrogenase revealed that o-glucuronate and L-gulonate, the product of D-glucuronate reduction, were also good substrates (19). The physical characteristics, as well as the substrate and inhibitor specificity of this enzyme, indicate that the ability to catalyze the oxidation of GHB probably represents a previously unreported activity for the NADP+-dependent oxidoreductase (EC 1.1.1.19) commonly known as Dglucuronte reductase (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We observed similar results during the formation of GBL/GHB in the hepatic S9, which indicates that the CYP2A6-mediated metabolic pathway of the furan ring of FT, followed by the sequential conversion of SA to GBL/GHB may contribute mainly to the formation of GBL/GHB under physiological conditions. The studies on endogenous GBL/ GHB catabolism have shown the oxidation of GBL/GHB to succinic semialdehyde by GHB dehydrogenase, followed by its oxidation to succinate by succinic semialdehyde dehydrogenase in mitochondria (Kaufman et al, 1979). Therefore, GBL/GHB generated after the administration of FT may be finally metabolized to succinate in mitochondria in vivo.…”
Section: Discussionmentioning
confidence: 99%